Neutron capture cross-sections for 159Tb isotope in the energy range of 5 to 17 MeV. (November 2018) - Soni, B.K.; Makwana, Rajnikant; Mukherjee, S.; Parashari, Siddharth; Suryanarayana, S.V.; Nayak, B.K.; Naik, H.; Mehta, M.
Abstract: The neutron capture cross-sections have been measured for the 159 Tb(n, γ) 160 Tb reaction at the spectrum average peak neutron energies of 5.08 ± 0.165, 12.47 ± 0.825, and 16.63 ± 0.95 MeV respectively. The experiment has been carried out using the standard neutron activation technique and off-line γ-ray spectrometry. The present measurement has been done for the energies where very few measured results are available in the data library. The results have been compared with ENDF/B-VII.1 and JENDL-4.0 data libraries. The present results have also been supported by theoretical predictions of nuclear model code TALYS 1.9. Detailed covariance analysis was carried out to find the uncertainty and the correlations among the measured cross-sections. Highlights: Tb being an excellent structural metal has several reactor and nuclear medicines based applications. Tb isotopes are of keen interest of study since they are widely used in nuclear medicine. Calculations have been performed within the framework of theoretical code Talys-1.9.